2011
DOI: 10.1186/1475-2840-10-20
|View full text |Cite
|
Sign up to set email alerts
|

Non-HDL-cholesterol as valid surrogate to apolipoprotein B100 measurement in diabetes: Discriminant Ratio and unbiased equivalence

Abstract: BackgroundApolipoprotein B100 (apoB) is a superior indicator of CV risk than total or LDL-C. Non-HDL-C represents a simple surrogate for apoB in hypertriglyceridemic and/or T2DM patients. ApoB and non-HDL-C show high correlation, although the degree of mutual concordance remains debated in CV risk evaluation.ObjectivesWe used the Discriminant Ratio (DR) methodology to compare the performance of non-HDL-C with that of apoB to rank diabetic patients according to dyslipidemia and to establish the underlying relat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
68
0
2

Year Published

2012
2012
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(74 citation statements)
references
References 25 publications
2
68
0
2
Order By: Relevance
“…Some authors believe apoB may provide a more complete picture of the lipoprotein profile as it will account for small, dense, more atherogenic particles [24]. Proponents of apoB also argue that the apoB concept is intrinsically easier to understand than nonHDL-C, which represents “a state of otherness” defined by a non-number, instead of a single atherogenic lipid variable [25-27]. …”
Section: Discussionmentioning
confidence: 99%
“…Some authors believe apoB may provide a more complete picture of the lipoprotein profile as it will account for small, dense, more atherogenic particles [24]. Proponents of apoB also argue that the apoB concept is intrinsically easier to understand than nonHDL-C, which represents “a state of otherness” defined by a non-number, instead of a single atherogenic lipid variable [25-27]. …”
Section: Discussionmentioning
confidence: 99%
“…Apolipoprotein B (apo B) is recognised as a risk factor of atherosclerotic disease, which may be superior in predictive value when compared to total and LDL cholesterol. Studies have shown that non-HDL-C is a simple surrogate of apo B levels, and that non-HDL-C shows a higher correlation with atherosclerotic cardiovascular disease than apo B [23].…”
Section: Discussionmentioning
confidence: 99%
“…8 Studies have shown Non-HDL-c being analogous to Apo-B in assessing atherogenic cholesterol and lipoprotein burden. 22 The apolipoprotein B assay is not routinely available because of its cost and general unfamiliarity with its interpretation outside of the research setting. Because of its simple calculation, the Non-HDL Cholesterol level is easily available with every lipid profile ordered and eliminating any additional costs.…”
Section: Discussionmentioning
confidence: 99%